A sensitive electrochemiluminescence aptasensor for Pb2+ detection in soil based on dual signal amplification strategy of aggregation-induced emission and resonance energy transfer. (20th July 2022) - Zhao, Wanlin; Liu, Xiaohong; Luo, Lijun; Li, Libo; You, Tianyan
Highlights: An on-off-on ECL aptasensor was developed based on dual signal amplification strategy. Aggregation-induced emission behavior of AuNCs provided the first signal-on state. The signal-off state was realized by resonance energy transfer between RhB and AuNCs. The Pb 2+ -induced second "signal-on" state was obtained by blocking RET process. The proposed aptasensor showed excellent analytical performance for Pb 2+ analysis. Abstract: In the present work, based on dual signal amplification strategy of aggregation-induced emission (AIE) and resonance energy transfer (RET), a highly sensitive and selective "on-off-on" output model electrochemiluminescence (ECL) aptasensor for Pb 2+ detection was constructed. In this approach, the first "signal-on" with a high and stable ECL signal was obtained by gold nanoclusters (AuNCs)-modified glassy carbon electrode surface with triethylamine as co-reactant. The AIE behaviour of AuNCs amplified ECL emission compared with AuNCs in solution. Later, the "signal-off" was activated by rhodamine B (RhB) quenched the AuNCs signal due to good spectral overlap between ultraviolet-visible absorption peak of RhB and ECL spectrum of AuNCs. The combination of dual signal amplification strategy provided a high signal to background ratio, leading to the improved sensitivity of the aptasensor. In the presence of Pb 2+, its specific binding to the aptamer induced the departure of RhB from the sensing interface, which resulted in the favourable recovery of ECL signal (Second "signal-off"). Therefore, the proposed ECL aptasensor exhibited a wide detection linear range from 1.0 × 10 −10 to 1.0 × 10 −4 M. Prospectively, the development dual signal amplification strategy could provide a novel sensing strategy for Pb 2+ detection. Graphical abstract: Image, graphical abstract